IBM Db2 : investigating automatic storage table spaces and data skew - Wangelien, George; Hoggard, Zachary (IBM redpaper., 2017)
The scope of this IBM® Redpaper"!publication is to provide a high-level overview of automatic storage table spaces, table space maps, table space extent maps, and physically unbalanced data across automatic storage table space containers (that is, data skew). The objective of this paper is to investigate causes of data skew and make suggestions for how to resolve it. This paper is for Database Administrators (DBAs) of IBM Db2®; the DBAs should have general Db2 knowledge and skills. The environment used for the creation of this document is Db2 Version 11.1, and an IBM AIX® operating system. This document is based on results of testing various scenarios